Solvothermal production of CdS nanorods using polyvinylpyrrolidone as a template - Titipun Thongtem (2018)
CdS nanorods were solvothermally produced using Cd(NO3)2 and S powder in ethylenediamine containing different amounts of polyvinylpyrrolidone (PVP). The phase with hexagonal structure was detected using Xray diffraction (XRD) and selected area electron diffraction (SAED). Their SAED patterns were in accordance with those of the simulations. Scanning and transmission electron microscopies (SEM and TEM) revealed the presence of CdS nanorods with their lengths influenced by different amounts of PVP. The nanorods were also characterized using high resolution TEM (HRTEM). They grew in the [001] direction normal to the (002) parallel crystallographic planes composing the nanorods. Raman spectra showed the 1LO (first harmonic) and 2LO (second harmonic) modes at the same wavenumbers although the products were produced under different conditions. ©2009 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.